PTEN depletion reduces H3K27me3 levels to promote epithelial-to-mesenchymal transition in epithelial colorectal cancer cells. - Ahmed H Ghobashi; Jane W Kimani; Christopher A Ladaika; Heather M O'Hagan (PLoS ONE)
Epithelial-to-mesenchymal (EMT) transition is one of the best-known examples of tumor cell plasticity. EMT enhances cancer cell metastasis, which is the main cause of colorectal cancer (CRC)-related mortality. Therefore, understanding underlying molecular mechanisms contributing to the EMT process is crucial to finding druggable targets and more effective therapeutic approaches in CRC. In this study, we demonstrated that phosphatase and tensin homolog (PTEN) knockdown (KD) induces EMT in epithelial CRC, likely through the activation of AKT. PTEN KD modulated chromatin accessibility and reprogrammed gene transcription to mediate EMT in epithelial CRC cells. Active AKT can phosphorylate enhancer of zeste homolog 2 (EZH2) on serine 21, which switches EZH2 from a transcriptional repressor to an activator. Interestingly, PTEN KD reduced the global levels of trimethylation of histone 3 at lysine 27(H3K27me3) in an EZH2-phosphorylation-dependent manner. Additionally, EZH2 phosphorylation at serine 21 reduced the interaction of EZH2 with another polycomb repressive complex 2 (PRC2) component, suppressor of zeste 12 (SUZ12), suggesting that the reduced H3K27me3 levels in PTEN KD cells were due to a disruption of the PRC2 complex. Overall, we demonstrated that PTEN KD modulates changes in gene expression to induce the EMT process in epithelial CRC cells by phosphorylating EZH2 and activates transcription factors such as activator protein 1 (AP1).